Molecular recognition of a lipophilic guanosine derivative in Langmuir films at the air-water interface - Čoga, Lucija; Spindler, Lea; Masiero, Stefano; Drevenšek-Olenik, Irena (Biochimica et biophysica acta. General subjects, 2017)
Molecular recognition of a lipophilic deoxyguanosine derivative at the air-water interface was investigated by film balance experiments and Brewster Angle Microscopy. Results showed that guanosine, despite strong tendency towards self-assembly, interacts with both complementary and noncomplementary liponucleosides (lipophilic derivatives of deoxycytidine and deoxythymidine). At surface pressures below 17mN/m, attractive and repulsive interactions were present in case of both mixed monolayers and were the strongest at guanosine molar fractions of 0.5 and 0.75. At higher values of surface pressure, deoxyguanosine-deoxycytidine interactions were strictly attractive and were present only for monolayers with guanosine molar fraction of 0.75. On the contrary, attractive and repulsive interactions remained present in case of deoxyguanosine-deoxythymidine mixed monolayers. This indicates that interactions between guanosine and cytidine are much stronger than guanosine-thymidine interactions. Interactions for none of the nucleoside pairs, however, are specific and π–stacking interactions between the aromatic planes of liponucleoside derivatives probably dominate over hydrogen bonding interactions. This article is part of a Special Issue entitled "G-quadruplex" Guest Editor: Dr. Concetta Giancola and Dr. Daniela Montesarchio. [Display omitted] •Guanosine at the air–water interface interacts with complementary as well as noncomplementary liponucleosides.•Film balance experiments and BAM Microscopy indicate that interactions between none of these nucleoside pairs are specific.•At larger surfaces pressures, π–π stacking interactions dominate over the hydrogen bonding interactions.